Altered cortical and subcortical local coherence in obstructive sleep apnea: a functional magnetic resonance imaging study. (21st November 2012) - Santarnecchi, Emiliano; Sicilia, Isabella; Richiardi, Jonas; Vatti, Giampaolo; Polizzotto, Nicola Riccardo; Marino, Daniela; Rocchi, Raffaele; Van De, Dimitri; Rossi, Alessandro
Summary Obstructive sleep apnea (OSA) syndrome is the most common sleep‐related breathing disorder, characterized by excessive snoring and repetitive apneas and arousals, which leads to fragmented sleep and, most importantly, to intermittent nocturnal hypoxaemia during apneas. Considering previous studies about morphovolumetric alterations in sleep apnea, in this study we aimed to investigate for the first time the functional connectivity profile of OSA patients and age–gender–matched healthy controls, using resting‐state functional magnetic resonance imaging (fMRI). Twenty severe OSA patients (mean age 43.2 ± 8 years; mean apnea–hypopnea index, 36.3 h−1) and 20 non‐apneic age–gender–body mass index (BMI)‐matched controls underwent fMRI and polysomnographic (PSG) registration, as well as mood and sleepiness evaluation. Cerebro‐cerebellar regional homogeneity (ReHo) values were calculated from fMRI acquisition, in order to identify pathology‐related alterations in the local coherence of low‐frequency signal (<0.1 Hz). Multivariate pattern classification was also performed using ReHo values as features. We found a significant pattern of cortical and subcortical abnormal local connectivity in OSA patients, suggesting an overall rearrangement of hemispheric connectivity balance, with a decrease of local coherence observed in right temporal, parietal and frontal lobe regions. Moreover, an increase in bilateral thalamic and somatosensory/motor cortices coherence have been found, a finding due possibly to an aberrant adaptation to incomplete sleep–wake transitions during nocturnal apneic episodes, induced by repetitive choke sensation and physical efforts attempting to restore breathing. Different hemispheric roles into sleep processes and a possible thalamus key role in OSA neurophysiopathology are intriguing issues that future studies should attempt to clarify.